Advances in management accounting. Vol. 18 - Epstein, Marc J.; Lee, John Y. (Advances in management accounting,, 2010)
Advances in Management Accounting" ("AMA") publishes well-developed articles on a variety of current topics in management accounting that are relevant to researchers in both practice and academe. As one of the premier management accounting research journals, "AMA" is well poised to meet the needs of management accounting scholars.